Los retos para la gestión y la docencia en la educación superior de América Latina - Llaque, J. Paul (2020)
At the beginning of the last decade of the twentieth cen-tury,  the business and praxis of university teaching were institutionally and continentally questioned. The so-called Bologna process has had a profound impact on higher education, not only in Europe, where it originated, but also in Latin America, through two superlative effects: the change of the traditional role of the teacher, and the global and local political demands. Before the question of what these effects implied, the thesis in this paper is that these effects have and continue to imply  five main challenges for both the business and praxis of teaching at the higher education level: i) the incorporation of the productive factor based on the growth and management of information in socioeconomic development; ii) the new information and communication technologies as accelerators and modifiers of  information management and communication processes; iii) a new professional profile based on educational goals and competencies; iv) a new paradigm in which the student becomes the center in the teaching-learning process, relegating the teacher to a role of facilitator; and v) the global scope of human activity that implies the internationalization of higher education. To prove this thesis, a double argumentative perspective is adopted. First, an analysis of each challenge; and, second, a proposal or consistent proposals to face it. Finally, a conclusive recount is made with an open horizon.